2018
DOI: 10.3389/fonc.2018.00546
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Number of Positive Pelvic Lymph Nodes as a Prognostic Factor in Cervical Cancer Treated With Definitive Concurrent Chemoradiotherapy or Intensity-Modulated Radiotherapy

Abstract: Background: This study aims to assess the prognostic significance of radiographic numbers of positive pelvic lymph nodes (PLNs) in patients with cervical cancer treated with definitive concurrent chemoradiotherapy (CCRT) or intensity-modulated radiotherapy (IMRT).Methods: We conducted a retrospective study that included 164 eligible adult patients with cervical cancer who were treated with definitive CCRT or IMRT at our institution from 2009 to 2016. After exclusion of 50 patients, a total of 114 patients whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…In particular, patients with 0, 1–2, and ≥3 suspected positive nodes experienced a 3 year overall survival of, respectively, 85.4% vs 82.4% vs 59.7% (p=0.035) 13. The radiographic number of suspected positive nodes ≥3 is an independent prognostic factor for overall survival, also at multivariate analysis 13. Here, our investigation corroborated these findings, investigating the role of pathological positive nodes in a larger group of patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In particular, patients with 0, 1–2, and ≥3 suspected positive nodes experienced a 3 year overall survival of, respectively, 85.4% vs 82.4% vs 59.7% (p=0.035) 13. The radiographic number of suspected positive nodes ≥3 is an independent prognostic factor for overall survival, also at multivariate analysis 13. Here, our investigation corroborated these findings, investigating the role of pathological positive nodes in a larger group of patients.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study we observed that, in addition to the presence of positive nodes, the number of positive nodes had an impact on patient outcomes, thus adding new information useful for assessing patient prognosis. Other investigators observed similar results focusing on patients with suspected positive nodes at radiological examination 13–15. Wang et al conducted a retrospective study that included 114 patients undergoing radiotherapy (with or without chemotherapy) for cervical cancer.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In recent years, the relationship between PLNs and the prognosis of cervical cancer patients has been clarified. In a study by Wang et al, patients treated with definitive concurrent chemoradiotherapy (CCRT) or intensity-modulated radiotherapy (IMRT) were included, and their results confirmed that the presence of PLNs (≥ 3) was an independent prognostic factor for OS, cancer-specific survival (CSS), and distant metastasis-free survival (DMFS) 17 . Similarly, Kwon et al also found that PLNs were associated with DMFS and disease-free survival (DFS) in patients with early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 92%
“…Different studies have selected different cutoff values when using the PLN system as the staging method 17 - 19 . In this study, we used the method of tree-based recursive partitioning, which can help select the parameters that provide the optimal split for censored data 30 .…”
Section: Discussionmentioning
confidence: 99%